2015
DOI: 10.2174/1389557515666151016125948
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers: Current State of Knowledge and Perspectives

Abstract: It has been over half a century since propranolol, the first beta-blocker, was developed for medical treatment. Since that time a large number of compounds from this group have been synthesised and many are now in clinical use. The structure, function, pharmacokinetics, and mechanism of beta-blockers have been established. The possibilities for their use in treating different conditions continue to evolve. Since the discovery of later generation beta-blockers, such as carvedilol and nebivolol, the search for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
0
19
0
5
Order By: Relevance
“…CVL blocks sympathetic neural activation via antagonism of β1-, β2-, and α1-adrenoreceptors and has shown greater cardiovascular benefits than traditional β-blockers in both humans and animals. Several in vivo and in vitro studies have demonstrated the cardioprotective, nephroprotective and hepatoprotective effects of CVL against various toxicant-induced preclinical models, and these effects are independent of its β-adrenergic blocking properties ( 1 ). Versatile anti-inflammatory effects of CVL were observed in both in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…CVL blocks sympathetic neural activation via antagonism of β1-, β2-, and α1-adrenoreceptors and has shown greater cardiovascular benefits than traditional β-blockers in both humans and animals. Several in vivo and in vitro studies have demonstrated the cardioprotective, nephroprotective and hepatoprotective effects of CVL against various toxicant-induced preclinical models, and these effects are independent of its β-adrenergic blocking properties ( 1 ). Versatile anti-inflammatory effects of CVL were observed in both in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenoceptor blockers can be divided into non-selective blockers for β1 and β2 receptors and β1-selective blockers, which have higher selective affinity for β1 receptors than for β2 receptors (114). The latter mainly slow down HR and decrease myocardial contractility when the sympathetic nervous system is activated but have a relatively small effect on the heart at rest (115).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Beta blokerler, hipertansiyon, konjestif kalp yetersizliği, kardiyak aritmiler ve angina pektoris gibi kardiyovasküler hastalıkların tedavisinde önemli bir yer tutarlar. [1][2][3] Beta blokerler genel olarak 3 gruba ayrılırlar. İlk grup, klasik beta blokerler olarak adlandırılan birinci nesil non-selektif ilaçlardır (propranolol, sotalol).…”
Section: öZetunclassified
“…Bu ilaçlar kalpte β-AR'lerin etkinliğini azalttıkları veya bloke ettikleri için, inhibitör etki (negatif inotrop, negatif kronotrop, negatif dromotrop etki) meydana getirirler. [1] Beta blokerlerin farmakolojik özellikleri Beta blokerlerin temel farmakolojik özellikleri arasında, selektiflik (seçicilik), intrinsik sempatomimetik etkinlik (İSE), ters agonizma, lipofilikliğin derecesi ve buna bağlı farmakokinetik farklar, membran stabilizasyonu ve melez (hibrid) etkinlik bulunmaktadır. [13] 1.…”
Section: Beta Adrenerjik Reseptörlerunclassified